Linoleic acid-derived lipid mediators increase in a female-dominated subphenotype of COPD. Issue 6 (10th March 2016) - Balgoma, David; Yang, Mingxing; Sjödin, Marcus; Snowden, Stuart; Karimi, Reza; Levänen, Bettina; Merikallio, Heta; Kaarteenaho, Riitta; Palmberg, Lena; Larsson, Kjell; Erle, David J.; Dahlén, Sven-Erik; et al.
Chronic obstructive pulmonary disease (COPD) is a leading cause of mortality; however, the role of inflammatory mediators in its pathobiology remains unclear. The aim of this study was to investigate the influence of gender in COPD on lipid mediator levels. Bronchoalveolar lavage fluid (BALF) and serum were obtained from healthy never-smokers, smokers and COPD patients (Global Initiative for Chronic Obstructive Lung Disease stage I–II/A–B) (n=114). 94 lipid mediators derived from the cytochrome-P450, lipoxygenase, and cyclooxygenase pathways were analysed by liquid chromatography-mass spectrometry. Multivariate modelling identified a 9-lipid panel in BALF that classified female smokers with COPD from healthy female smokers (p=6×10 −6 ). No differences were observed for the corresponding male population (p=1.0). These findings were replicated in an independent cohort with 92% accuracy (p=0.005). The strongest drivers were the cytochrome P450-derived epoxide products of linoleic acid (leukotoxins) and their corresponding soluble epoxide hydrolase (sEH)-derived products (leukotoxin-diols). These species correlated with lung function (r=0.87; p=0.0009) and mRNA levels of enzymes putatively involved in their biosynthesis (r=0.96; p=0.003). Leukotoxin levels correlated with goblet cell abundance (r=0.72; p=0.028). These findings suggest a mechanism by which goblet cell-associated cytochrome-P450 and sEH activity produce elevated leukotoxin-diol levels, which play a putative role in the clinical manifestations of COPD in a female-dominated disease sub-phenotype. Linoleic acid-derived lipids in BALF may indicate the transition from healthy smoker to COPD in a female subphenotype http://ow.ly/XowqN